Design and experiment of spray and rotary tillage combined disinfection machine for soil - Wang, Jinwu; Yang, Wenpan; Sun, Xiaobo; Li, Xiang; Tang, Han (International Journal of Agricultural and Biological Engineering, 2019)
A spray and rotary tillage combined disinfection machine for soil was designed to solve the serious problems of plant diseases and insect pests, and it was divided into two operations which were soil disinfection and rotary tillage. The main structure and working principle of this machine were illustrated and analyzed. The reasonable structural parameters of the key parts of this machine were optimized, such as spraying disinfection system and rotary tillage land preparation system. To optimize the working performance and obtain better operation parameters, the orthogonal experiments were carried out to analyze the influences of three factors (forward speed of driving machine, rotational speed of rotary tillage, and working pressure) on the working performance. The mixing uniformity coefficient and the variation coefficient of spraying were selected for evaluating working performance. The range analysis and variance analysis were studied based on experimental data. The results showed that, the mixing uniformity coefficient of spraying was 93.95% and the variation coefficient was 6.01% with a working speed of 3 km/h, rotational speed of 2000 r/min and working pressure of 2.0 MPa. The machine can meet the agronomic requirements of disinfection and plowing, which was designed simply, compactly and strong applicability. The results can provide a guidance and technical support for preventing the plant diseases and insect pests, developing sustainable and ecological agriculture and improving the efficiency of compound cultivation. Keywords: agricultural machine, soil disinfection, spray, rotary tillage, compound operation DOI: 10.25165/j.ijabe.20191201.3640 Citation: Wang J W, Yang W P, Sun X B, Li X, Tang H. Design and experiment of spray and rotary tillage combined disinfection machine for soil. Int J Agric & Biol Eng, 2019; 12(1): 52–58.